Syntactic Study of Essays by Grade VII Junior High School Students Undiksha Singaraja Laboratory - Ida Bagus Putrayasa; I Nengah Suandi (Journal of Linguistica, 2024)
The study of seventh grade students' essays at Undiksha Singaraja Laboratory School is important to understand the use of sentence types, sentence unity, and sentence structure. This study aims to describe (1) sentence types, (2) sentence unity, and (3) sentence structure in students' essays. The data collection method used document recording and was analyzed qualitatively. The results showed that students used 107 single sentences and 99 compound sentences, reflecting a balance between the two. Sentence unity is shown by 186 sentences that have clear subject-predicate relationships, while there are 11 sentences without subjects and predicates, 8 sentences only contain predicates, and 1 sentence only has a subject. The varied sentence structures show the students' ability to construct sentences well. This research not only improves the understanding of students' writing ability, but also contributes to the field of syntax with insights into sentence formation and coherence among junior high school students